Concentration of particulate matter, CO and CO2 in selected schools in Malaysia. (May 2015) - Yang Razali, Nikmatun Yusro; Latif, Mohd Talib; Dominick, Doreena; Mohamad, Noorlin; Sulaiman, Fazrul Razman; Srithawirat, Thunwadee
Abstract: Good Indoor Air Quality (IAQ) is important to ensure improved performance and productivity of students and teachers. Research was conducted at three selected schools in semiurban areas of Bandar Baru Bangi and Putrajaya, Malaysia to investigate the influence of the local surroundings on the IAQ in the school classrooms. The concentrations of gas pollutants (CO, CO2 ) and particulate matter (PM) (PM10, PM2.5 and PM1 ) have been determined using automatic portable indoor air spectrometers. The results show that the overall average concentrations of the main parameters recorded inside the schools were 31 μg m −3 (PM10 ), 18 μg m −3 (PM2.5 ), 16 μg m −3 (PM1 ), 502 ppm (CO2 ) and 0.3 ppm (CO). These concentrations were still below the recommended values suggested by the Malaysian Department of Safety and Health (DOSH), the Singapore National Environmental Agency (NEA) and the Hong Kong IAQ Guidelines for Offices and Public Places. In most cases, there were significant correlations ( p  < 0.01) between air pollutants and meteorological factors such as temperature and relative humidity in the classrooms. The results of Indoor/Outdoor (I/O) ratios demonstrated that the concentration of indoor air pollutants in different classrooms was not necessarily influenced by outdoor air pollutants. Highlights: We measured the concentration of particulate matter, CO2 and CO in classrooms. Meteorological factors and outdoor air pollutants were also determined. Indoor air pollutants not necessarily influence by outdoor air pollutants. Temperature and relative humidity influence the indoor air pollutant concentrations.